2006
DOI: 10.1111/j.1467-8624.2006.00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Race, Ethnicity, and Culture in Child Development: Contemporary Research and Future Directions

Abstract: The editors of this special issue reflect on the current status and future directions of research on race, ethnicity, and culture in child development. Research in the special issue disentangles race, ethnicity, culture, and immigrant status, and identifies mediators of sociocultural variables on developmental outcomes. The special issue includes important research on normal development in context for ethnic and racial minority children, addresses racial and ethnic identity development, and considers intergrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
181
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(192 citation statements)
references
References 47 publications
3
181
0
4
Order By: Relevance
“…Most authors agree that ethnic identity development is dynamic, and emerges during adolescence (Phinney, 1990;Quintana et al, 2006;Yip, Seaton, & Sellers, 2006). Ethnic identity formation takes place over time, as ethnic group members explore and make decisions about the role ethnicity plays in their lives.…”
Section: Ethnic Identity Developmentmentioning
confidence: 99%
“…Most authors agree that ethnic identity development is dynamic, and emerges during adolescence (Phinney, 1990;Quintana et al, 2006;Yip, Seaton, & Sellers, 2006). Ethnic identity formation takes place over time, as ethnic group members explore and make decisions about the role ethnicity plays in their lives.…”
Section: Ethnic Identity Developmentmentioning
confidence: 99%
“…Accompanying the growth of ethnic and racial groups in the United States, research over the last 30 years has focused on the socialization processes of ethnic and racial minority families (Quintana et al, 2006). Researchers have revealed that socializing youth about ethnicity and race (i.e., ethnicracial socialization) is a predominant component of socialization in ethnic and racial minority families (Garcia Coll et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…While ethnic and cultural socialization literature argues that second generation children learn about their parents' immigrant cultures through daily practices and routinized behaviors Quintana et al 2006), the excerpt above demonstrates that teaching about a culture "left behind" can also be much more deliberate. Part of a larger study on Asian Indian families and immigration, this paper utilizes ethnographic data, home visits, and interviews with parents to nuance childhood socialization research by highlighting immigrant parents' efforts of ethnic and cultural socialization as strategic.…”
Section: Introductionmentioning
confidence: 99%
“…Markset al (2007) and Quintana et al (2006) argue that among ethnic minority children and adolescents, higher levels of ethnic pride may help them cope with discrimination in school, and other daily stresses. And still, several other studies suggest that cultural socialization is associated with higher self-esteem in peer groups (Constantine & Blackmon 2002;Kiang et al 2006), as well as better cognitive outcomes and anger management (Stevenson 1997).…”
Section: Introductionmentioning
confidence: 99%